Transcranial Magnetic Stimulation as a Tool to Investigate Motor Cortex Excitability in Sport - Moscatelli, Fiorenzo (Brain Sci, 2021)
Transcranial magnetic stimulation, since its introduction in 1985, has brought important innovations to the study of cortical excitability as it is a non-invasive method and, therefore, can be used both in healthy and sick subjects. Since the introduction of this cortical stimulation technique, it has been possible to deepen the neurophysiological aspects of motor activation and control. In this narrative review, we want to provide a brief overview regarding TMS as a tool to investigate changes in cortex excitability in athletes and highlight how this tool can be used to investigate the acute and chronic responses of the motor cortex in sport science. The parameters that could be used for the evaluation of cortical excitability and the relative relationship with motor coordination and muscle fatigue, will be also analyzed. Repetitive physical training is generally considered as a principal strategy for acquiring a motor skill, and this process can elicit cortical motor representational changes referred to as use-dependent plasticity. In training settings, physical practice combined with the observation of target movements can enhance cortical excitability and facilitate the process of learning. The data to date suggest that TMS is a valid technique to investigate the changes in motor cortex excitability in trained and untrained subjects. Recently, interest in the possible ergogenic effect of non-invasive brain stimulation in sport is growing and therefore in the future it could be useful to conduct new experiments to evaluate the impact on learning and motor performance of these techniques.